Human amniotic mesenchymal stem cells-derived conditioned medium and exosomes alleviate oxidative stress-induced retinal degeneration by activating PI3K/Akt/FoxO3 pathway - Zhe-Qing Peng; Xiao‐Hui Guan; Zhenping Yu; Jie Wu; Xin‐Hao Han; Minghui Li; Xin-Hui Qu; Zhiping Chen; Xiao‐Jian Han; X. Wang (2024)
Age-related macular degeneration (AMD) is the leading cause of vision loss among the elderly, which is primarily attributed to oxidative stress-induced damage to the retinal pigment epithelium (RPE). Human amniotic mesenchymal stem cells (hAMSC) were considered to be one of the most promising stem cells for clinical application due to their low immunogenicity, tissue repair ability, pluripotent potential and potent paracrine effects. The conditional medium (hAMSC-CM) and exosomes (hAMSC-exo) derived from hAMSC, as mediators of intercellular communication, play an important role in the treatment of retinal diseases, but their effect and mechanism on oxidative stress-induced retinal degeneration are not explored. Here, we reported that hAMSC-CM alleviated H